Amaranth—Amaranthus spp. - James M. Stephens (EDIS)
This document provides an overview of various species of the genus Amaranthus, commonly known as amaranths. It details their cultivation, particularly in Florida, highlighting their rapid growth and resilience in warm climates. The article describes different varieties, including those with green, red, and variegated leaves, and their uses as leafy greens and grain. It also notes the nutritional benefits of amaranth, particularly its high lysine content, and its culinary applications, such as in breads and cereals. The document emphasizes the importance of proper cultivation to avoid pest issues and maximize yield. Original publication date April 1994.